2012
DOI: 10.1097/ncq.0b013e31823f8573
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Management of Postoperative Delirium Among Older Patients on an Orthopedic Surgical Unit

Abstract: Delirium is an acute state of confusion that is often seen in older patients after major orthopedic surgical procedures. It is associated with increased costs of care, morbidity, delayed functional recovery, and prolonged hospital stay. Identification of predictive risk factors, early diagnosis and treatment, and implementation of environmental controls can minimize the impact of postoperative delirium. This project measured pre- and post intervention compliance with best practice in the prevention and managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…Sockalingam et al .’s () review concluded that the extent to which inter‐professional activities are incorporated into IPE sessions influences the likelihood of benefits for patients from such education, via practice change. Two previous studies achieving practice change more actively engaged the staff; one included bedside coaching and the other involved unit‐based, inter‐professional, collaborative decision‐making (Sykes, ; Gordon et al ., ). Providing IPE was challenging in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sockalingam et al .’s () review concluded that the extent to which inter‐professional activities are incorporated into IPE sessions influences the likelihood of benefits for patients from such education, via practice change. Two previous studies achieving practice change more actively engaged the staff; one included bedside coaching and the other involved unit‐based, inter‐professional, collaborative decision‐making (Sykes, ; Gordon et al ., ). Providing IPE was challenging in this study.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 It has been suggested that the correction of modifiable risk factors is effective in delirium prevention and delirium prevention programs can succeed in decreasing the duration of delirium. 11,12 However, general prevention for all surgical patients is not cost-effective. Thus, a predictive model for delirium is necessary to identify high-risk patients for monitoring and proactive implementation of preventive strategies.…”
Section: Introductionmentioning
confidence: 99%
“…월 동안 사망률이 2.5배 높았고, 퇴원 후 일상생활기능의 감소 도 2.2배 높았으며 (Abelha et al, 2013), 재원기간도 평균 4 일 이상 길게 보고되었다 (Robinson et al, 2009) (Robinson et al, 2009;Staus, 2011;van Meenen, van Meenen, de Rooij, & ter Riet, 2014), 고령으로 인한 취약한 기저질환 동반 (Inouye et al, 2014), 수술 후 지연되는 신체 회복 상태 (Bellelli et al, 2014), 수술로 인해 발생하는 기동력 장애 (Chung et al, 2011), 수술 후 발생하는 심각한 통증 (Staus, 2011) (Sykes, 2012).…”
Section: 수술 후 섬망이 발생한 환자는 발생하지 않은 환자에 비해 6개unclassified